Mitigation of voltage sags/swells using dynamic voltage restorer based on DQO algorithm / Mohamad Shahrun Azizan - Azizan, Mohamad Shahrun (2009)
This paper presents the application of dynamic voltage restorers (DVR) on power distribution systems for mitigation of voltage sags/swells at critical loads. Voltage sags is short reduction voltage from nominal voltage, occur in a short time which can cause damage and loss of production especially in industrial sector. Voltage swells is a sudden increasing of supply voltage in rms voltage at network fundamental frequency cause by energizing large capacitor or switching off a large inductive load. A dynamic voltage restore based on the dqo algorithm is discussed. The control scheme is very effective to detect any disturbance in low voltage distribution systems. Simulation results using Matlab/Simulink are presented to verify the effectiveness.